Orchestrating Research Culture: Principal's Strategic Planning in Institutionalizing Mandatory Youth Scientific Work Literacy - Sugiyanti; Ngurah Ayu Nyoman Murniati; Bunyamin (Jurnal Pendidikan Indonesia, 2026)
This study is driven by the urgency to transform scientific activities in schools from extracurricular practices into an institutionalized academic culture. The study aims to analyze the principal’s strategic planning in institutionalizing the Youth Scientific Work (KIR) literacy program as a mandatory academic requirement. This research employs a qualitative approach with a case study method. The subjects of the study include the principal, teachers, and students involved in the KIR program. Data were collected through in-depth interviews, participant observation, and documentation studies using interview guidelines, observation sheets, and document analysis instruments. Data validity was ensured through source and technique triangulation. Data analysis was conducted using the interactive model by Miles and Huberman, including data collection, condensation, display, and conclusion drawing. The findings reveal that the principal’s strategic orchestration involves four key stages: environmental analysis to map research ecosystems and global challenges; organizational analysis to assess human resources and scientific infrastructure; formulation of KIR program objectives integrated into the curriculum; and determination of operational strategies that engage the entire school community. The study concludes that institutionalizing a research culture requires strong strategic intent and systematic planning from the principal. This research implies that strategic leadership plays a critical role in embedding sustainable scientific literacy within school systems.